Polysaccharide acrylic resin and preparation method thereof

By transforming coffee residue into polysaccharides by multiple steps, and reaction with acrylic monosiophage to form a wrong molecular chain, it solves the problem of high cost of vegetable oil, prepares high -strength, biodegradable polysaccharide acrylic resin, and realizes cheap biomass materials. Efficient use.

CN119350560AInactive Publication Date: 2025-01-24GUANGDONG LIYU MATERIAL TECHNOLOGY CO LTD

Patent Information

Application Number
CN202411656245.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-01-24
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

In the prior art, vegetable oils are produced as raw materials for synthetic resins with high cost and are difficult to effectively utilize cheap and widely sourced biological materials.

Method used

By converting coffee residue through miscellaneous, deprikimal quality, acid hydrolysis, and acrylic acid, it is converted into high cellulose and semi -cellulose content, and then hydrolyzed into a highly chemical reactive polysaccharide, and finally acrylic acid The single reaction forms a staggered molecular chain to prepare polysaccharide acrylic resin.

Benefits of technology

It is possible to use cheap biomaterial coffee grounds as raw material to prepare biodegradable acrylic resin with high strength performance, reducing production costs and reducing environmental pollution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119350560A_ABST
    Figure CN119350560A_ABST
Patent Text Reader

Abstract

The invention relates to polysaccharide acrylic resin and a preparation method thereof, and belongs to the technical field of intersection of high value-added utilization of biomass resources and acrylic resin. The polysaccharide acrylic resin is prepared from the following components in parts by weight: 40 to 50 parts of acrylic modified polysaccharide, 10 to 30 parts of acrylic monomer, 20 to 30 parts of polybasic acid, 10 to 15 parts of polyhydric alcohol, 3 to 5 parts of emulsifier, 0.4 to 0.6 part of initiator, 0.1 to 0.3 part of defoaming agent, 1 to 3 parts of catalyst and 60 to 80 parts of deionized water. Coffee grounds are subjected to impurity removal, lignin removal, acid hydrolysis and acrylic acid group modification, so that the coffee grounds are converted into delignification coffee grounds with high cellulose and hemicellulose content, then the delignification coffee grounds are hydrolyzed into polysaccharide with high chemical reaction activity, finally acrylic acid group modified polysaccharide is formed, acrylic acid groups are grafted on molecular chains, and the modified polysaccharide is obtained. Polysaccharide molecules have a large amount of hydroxyl groups which further react with polybasic acid to form a net-shaped cross-linked molecular chain, so that the acrylic resin after film formation has higher strength performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of high value-added utilization of biomass resources and cross-technical field of acrylic resin, and in particular relates to a polysaccharide acrylic resin and a preparation method thereof. Background Art

[0002] In the field of coating applications, bio-based materials, especially vegetable oils, have been widely used to prepare new green and environmentally friendly coatings. This is because vegetable oils are non-toxic, low volatile, biodegradable, and have abundant and readily available raw materials. Since the 19th century, people have conducted a series of studies on vegetable oil-based polymers. For example, triglycerides in vegetable oils are hydrolyzed with glycerol to obtain monoglycerides for the preparation of alkyd resins; drying oils or fatty acids are first maleic anhydride-treated and then transesterified with epoxy prepolymers to prepare fatty acid-modified epoxy coatings; soybean oil is epoxidized and then combined with acrylates to prepare epoxidized soybean oil acrylate resins; monoglycerides are also a polyol that can react with diisocyanates to prepare polyurethanes. The vegetable oils used to prepare water-based polyurethanes include sunflower oil, castor oil, rapeseed oil, soybean oil, etc.; tung oil is directly formed into a biodegradable coating after thermal cross-linking polymerization.

[0003] In the field of coating applications, bio-based materials, especially vegetable oils, have been widely used to prepare new green and environmentally friendly coatings. This is because vegetable oils are non-toxic, low volatile, biodegradable, and have abundant and readily available raw materials. Since the 19th century, people have conducted a series of studies on vegetable oil-based polymers. For example, triglycerides in vegetable oils are hydrolyzed with glycerol to obtain monoglycerides for the preparation of alkyd resins; drying oils or fatty acids are first maleic anhydride-treated and then transesterified with epoxy prepolymers to prepare fatty acid-modified epoxy coatings; soybean oil is epoxidized and then combined with acrylates to prepare epoxidized soybean oil acrylate resins; monoglycerides are also a polyol that can react with diisocyanates to prepare polyurethanes. The vegetable oils used to prepare water-based polyurethanes include sunflower oil, castor oil, rapeseed oil, soybean oil, etc.; tung oil is directly formed into a biodegradable coating after thermal cross-linking polymerization. However, the demand for vegetable oil as a dietary staple of human beings is also increasing. Therefore, the production cost of using vegetable oil as a raw material for synthetic resin is relatively high. Therefore, it is urgent to explore a method for synthesizing the resins needed by people using cheap and widely available biomaterials.

[0004] Coffee is one of the three major beverages in the world. Between 2000 and 2012, global coffee production increased by nearly 17%. According to the International Coffee Organization, the global coffee industry processed about 9.6 million tons in 2017. In the coffee production steps such as roasting and brewing, more than 90% of the initial dry coffee mass is produced in the form of coffee grounds. The waste generated from coffee in coffee-producing countries accounts for more than 50% of the total fruit residues. Therefore, coffee grounds are a kind of agricultural and forestry waste with huge output. For this reason, coffee factories need to spend a certain cost to treat coffee grounds. The composition of coffee grounds is relatively complex, mainly including lignin, cellulose, hemicellulose and lipids, as well as a small amount of protein, polyphenols and minerals. The lignin content is about 30wt%, and the total content of cellulose and hemicellulose is about 40-50wt%. Resource utilization of coffee grounds can not only reduce the pollution of coffee grounds to the environment, but also bring certain economic benefits. Summary of the invention

[0005] In view of the above shortcomings, the object of the present invention is to provide a polysaccharide acrylic resin and a preparation method thereof, wherein coffee grounds are subjected to impurity removal, delignification, acid hydrolysis and acrylic acid group modification, so that the coffee grounds are converted into delignified coffee grounds with high cellulose and hemicellulose content, and then hydrolyzed into polysaccharides with high chemical reactivity, and finally acrylic acid group-modified polysaccharides are formed, such as Figure 1 As shown, acrylic acid groups are grafted on the molecular chains and react with acrylic acid monomers to form staggered molecular chains, while the polysaccharide molecules have a large number of hydroxyl groups that further react with polyacids to form network cross-linked molecular chains, so that the acrylic resin after film formation has higher strength performance. At the same time, the acrylic resin prepared by the present invention uses bio-based materials as raw materials and is biodegradable. It will automatically degrade in the environment after later use and will not cause a burden to the environment.

[0006] The specific technical solutions are as follows:

[0007] A polysaccharide acrylic resin, which is composed of 40-50 parts of acrylic acid-modified polysaccharide, 10-30 parts of acrylic acid monomer, 20-30 parts of polyacid, 10-15 parts of polyol, 3-5 parts of emulsifier, 0.4-0.6 parts of initiator, 0.1-0.3 parts of defoamer, 1-3 parts of catalyst and 60-80 parts of deionized water in parts by weight; the preparation of acrylic acid-modified micro-nano coffee grounds comprises the following steps:

[0008] S1 impurity removal: soaking coffee grounds in n-hexane, with a mass volume ratio of coffee grounds to n-hexane of 5-10 g:1-10 mL, reacting at 20-30° C. and a mechanical stirring speed of 200-500 rpm for 3-6 hours, filtering and removing the filtrate to obtain the impurity-removed coffee grounds;

[0009] S2 Delignification: Soak the coffee grounds after impurity removal in a sodium hydroxide solution with a concentration of 5wt% to 12wt%, with a mass volume ratio of coffee grounds to sodium hydroxide of 1 to 10g:1 to 5mL, react at 80 to 100°C and a mechanical stirring speed of 500 to 1000 rpm for 1 to 3 hours, filter, and collect the filter residue; soak the filter residue in 3 to 10wt% hydrogen peroxide, with a mass volume ratio of filter residue to hydrogen peroxide of 5 to 10g:1 to 5mL, adjust the pH value of the mixed solution to 10 to 12, and react at 80 to 100°C for 2 to 5 hours until the filter residue turns white to obtain delignified coffee grounds;

[0010] S3 acid hydrolysis: soak the delignified coffee grounds in a dilute hydrochloric acid solution with a concentration of 1M to 3M, react for 3 to 5 hours at a temperature of 30 to 40°C and a stirring speed of 200 to 500 rpm, filter out the filtrate, wash with deionized water until the filtrate is neutral, and dry to obtain polysaccharides;

[0011] S4 acrylic acid-modified polysaccharide: Into a multifunctional reactor, add 30-40 parts of polysaccharide, 20-30 parts of organic acrylic acid aldehyde, and 10-20 parts of 1,4-dioxane in order by mass, heat the reactants to 50-60°C at a stirring speed of 500-1000 rpm, and react for 4-6 hours until the reaction is completed; then use reduced pressure distillation to heat to 30-40°C and a pressure of 55-65 mbar for distillation, evaporate 1,4-dioxane and unreacted organic acrylic acid aldehyde and collect and store them, filter the distilled solution, collect the filter residue, and air-dry the filter residue at 30°C to obtain purified acrylic acid-modified polysaccharide.

[0012] In some embodiments, the organic acrylic aldehyde may be a combination of one or more of 3-formylbutenoic acid, 4-formylpentenoic acid, and 5-formylhexenoic acid.

[0013] In some embodiments, the acrylic monomer may be one or more combinations of methyl acrylate, ethyl acrylate, butyl acrylate, methacrylic acid, methyl methacrylate, isobutyl acrylate, hexyl acrylate, isooctyl acrylate, and lauryl acrylate.

[0014] In some embodiments, the polyacid may be one or more combinations of phthalic anhydride, terephthalic acid, acetic anhydride, and maleic anhydride.

[0015] In some embodiments, the polyol may be a combination of one or more of glycerol, pentaerythritol, trimethylolethane, and trimethylolpropane.

[0016] In some embodiments, the emulsifier may be a combination of one or more of sodium stearate, sodium stearyl glutamate and potassium cetyl phosphate.

[0017] In some embodiments, the initiator can be a combination of one or more of benzoyl peroxide, tert-butyl hydroperoxide, and tert-amyl peroxyacetate.

[0018] In some embodiments, the defoaming agent may be a combination of one or more of sucrose fatty acid esters and polyglycerol fatty acid esters.

[0019] In some embodiments, the catalyst may be antimony trioxide, Sn(Oct)2, or a combination thereof.

[0020] The present invention also provides a method for preparing the above-mentioned polysaccharide acrylic resin, the preparation method comprising the following steps:

[0021] S5: In a multifunctional reactor, acrylic acid monomer, deionized water, emulsifier and defoamer are added in sequence according to the formula weight, and then stirred at a speed of 500 to 1000 rpm for 10 to 30 minutes while introducing nitrogen to obtain an emulsion, and then acrylic acid-modified polysaccharide is added, and stirring is continued for 10 to 30 minutes to obtain a uniform mixed solution, and nitrogen is continued to be introduced for 5 to 10 minutes;

[0022] S6: Stop introducing nitrogen, heat to 100-110°C, then add the formulated amount of initiator, continue stirring evenly to initiate the polymerization reaction, and keep warm for 2 hours, during which time the generated water vapor is separated by a water separator;

[0023] S7 After the reaction is completed, add polyacid, polyol and catalyst in sequence, continue to heat to 140-160°C, keep warm for 0.5-1 hour, so that the materials are completely dissolved to form a uniform solution, and then continue to heat to 180-200°C to initiate esterification reaction, react for 4-6 hours, during which the generated water vapor is separated by a water separator;

[0024] S8 After the reaction is completed, samples are taken every 30 minutes for acid value testing. When the acid value is 50-60 mg KOH / g, the reaction is stopped; the temperature is lowered to 50°C and kept warm, and dispersed for 30-60 minutes at a stirring speed of 8000-10000 rpm, and deionized water is added in a formula amount so that the viscosity of the mixed solution is 9000-12000 cps / 25°C, and then the stirring is continued for 30-60 minutes at a stirring speed of 800-1000 rpm to obtain a polysaccharide acrylic resin.

[0025] The present invention has the following advantages:

[0026] (1) Using coffee grounds, a byproduct of the coffee industry, as production raw materials has low cost and can reduce the pollution of coffee grounds to the environment, realizing high-value utilization of waste, and providing a new way to utilize coffee grounds;

[0027] (2) The formula does not involve the use of organic solvents, and the subsequent use of acrylic resin coatings will not produce gases harmful to human health, which is in line with the green and environmentally friendly production concept;

[0028] (3) The present invention converts coffee grounds into delignified coffee grounds with high cellulose and hemicellulose content by removing impurities, delignifying, acid hydrolyzing and modifying with acrylic acid groups, and then hydrolyzing them into polysaccharides with high chemical reactivity, and finally forming acrylic acid-modified polysaccharides, grafting acrylic acid groups on the molecular chains, reacting with acrylic acid monomers to form staggered molecular chains, and the polysaccharide molecules have a large number of hydroxyl groups that further react with polyacids to form network cross-linked molecular chains, so that the acrylic resin after film formation has higher strength performance;

[0029] (4) The acrylic resin prepared by the present invention uses bio-based raw materials and is biodegradable. It will automatically degrade in the environment after use and will not cause any burden to the environment. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 Molecular schematic diagram of the chemical reaction formula for preparing polysaccharide-based acrylic resin from delignified coffee grounds;

[0031] Figure 2 From left to right are scanning electron microscope images of coffee grounds before treatment and coffee grounds after treatment in Examples 1 to 3;

[0032] Figure 3 Optical photographs of the polysaccharide acrylic resins prepared in Examples 12 to 14;

[0033] Figure 4 Biodegradation test results of the polysaccharide acrylic resin prepared in Examples 12 to 14. DETAILED DESCRIPTION

[0034] The following will be combined with the drawings, technical process steps, specific implementation conditions and materials in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0035] Example 1

[0036] Soak the coffee grounds in n-hexane, the mass volume ratio of coffee grounds to n-hexane is 5g:1mL, react at 20℃, mechanical stirring speed is 500 rpm for 3 hours, filter and remove the filtrate to obtain the coffee grounds after impurities are removed. Soak the coffee grounds after impurities in a 5wt% sodium hydroxide solution, the mass volume ratio of coffee grounds to sodium hydroxide is 1g:2mL, react at 100℃, mechanical stirring speed is 500 rpm for 3 hours, filter, and collect the filtrate and filter residue separately. Soak the filter residue in 3wt% hydrogen peroxide, the mass volume ratio of the filter residue to hydrogen peroxide is 5g:5mL, adjust the pH value of the mixed solution to 12, and react at 100℃ for 2 hours until the filter residue turns white.

[0037] The microstructure of the original coffee grounds and the treated coffee grounds was characterized by scanning electron microscopy. Figure 2 As shown, the surface of the coffee grounds before treatment is non-porous and filled with lignin, lipids, proteins and other substances, while the surface of the coffee grounds after treatment is honeycomb-shaped with a rich pore structure, indicating that lignin, lipids, proteins and other substances have been removed.

[0038] The contents of lignin (acid-insoluble lignin), cellulose and hemicellulose in the coffee grounds before and after treatment were determined according to GB / T2677.8-947, GB / T 2677.10-19957 and the nitric acid-ethanol method, respectively. The results are shown in Table 1. The results show that after treatment, a large amount of lignin was removed, while a large amount of cellulose and hemicellulose were retained.

[0039] Table 1 Contents of lignin, cellulose and hemicellulose in coffee grounds before and after treatment

[0040] Sample name Lignin(%) Hemicellulose (%) Cellulose(%) Pre-processed coffee grounds 30.3±1.5 51.5±0.5 18.2±0.8 Processed coffee grounds 4.8±0.5 53.6±0.7 41.8±0.5

[0041] Example 2

[0042] Soak the coffee grounds in n-hexane, the mass volume ratio of coffee grounds to n-hexane is 7g:8mL, react at 30°C, mechanical stirring speed is 200 rpm for 6 hours, filter and remove the filtrate to obtain the coffee grounds after impurities are removed. Soak the coffee grounds after impurities in a 12wt% sodium hydroxide solution, the mass volume ratio of coffee grounds to sodium hydroxide is 10g:5mL, react at 90°C, mechanical stirring speed is 1000 rpm for 3 hours, filter, and collect the filtrate and residue separately. Soak the residue in 10wt% hydrogen peroxide, the mass volume ratio of the residue to hydrogen peroxide is 5g:5mL, adjust the pH value of the mixed solution to 11, and react at 90°C for 5 hours until the residue turns white.

[0043] Table 2 Contents of lignin, cellulose and hemicellulose in coffee grounds before and after treatment

[0044] Sample name Lignin(%) Hemicellulose (%) Cellulose(%) Pre-processed coffee grounds 30.3±1.5 51.5±0.5 18.2±0.8 Processed coffee grounds 3.5±1.09 52.7±1.27 44.3±0.9

[0045] The microscopic morphology of the treated coffee grounds was characterized by scanning electron microscopy. Figure 2 As shown, the surface of the treated coffee grounds is honeycomb-shaped with a rich pore structure, indicating that substances such as lignin, lipids, and proteins have been removed.

[0046] The contents of lignin (acid-insoluble lignin), cellulose and hemicellulose in the coffee grounds before and after treatment were determined according to GB / T2677.8-947, GB / T 2677.10-19957 and the nitric acid-ethanol method, respectively. The results are shown in Table 2. The results show that after treatment, a large amount of lignin was removed, while a large amount of cellulose and hemicellulose were retained.

[0047] Example 3

[0048] Soak the coffee grounds in n-hexane with a mass volume ratio of coffee grounds to n-hexane of 10g:10mL, react at 30°C and a mechanical stirring speed of 200 rpm for 4 hours, filter and remove the filtrate to obtain the coffee grounds after impurities are removed. Soak the coffee grounds after impurities in a sodium hydroxide solution with a concentration of 8wt%, with a mass volume ratio of coffee grounds to sodium hydroxide of 5g:5mL, react at 80°C and a mechanical stirring speed of 500 rpm for 3 hours, filter, and collect the filtrate and residue separately. Soak the residue in 7wt% hydrogen peroxide with a mass volume ratio of the residue to hydrogen peroxide of 10g:5mL, adjust the pH value of the mixed solution to 10, and react at 80°C for 4 hours until the residue turns white;

[0049] The microstructure of the original coffee grounds and the treated coffee grounds was characterized by scanning electron microscopy. Figure 2 As shown, the surface of the coffee grounds before treatment is non-porous and filled with lignin, lipids, proteins and other substances, while the surface of the coffee grounds after treatment is honeycomb-shaped with a rich pore structure, indicating that lignin, lipids, proteins and other substances have been removed.

[0050] The contents of lignin (acid-insoluble lignin), cellulose and hemicellulose in the coffee grounds before and after treatment were determined according to GB / T2677.8-947, GB / T 2677.10-19957 and the nitric acid-ethanol method, respectively. The results are shown in Table 3. The results show that after treatment, a large amount of lignin was removed, while a large amount of cellulose and hemicellulose were retained.

[0051] Table 3 Contents of lignin, cellulose and hemicellulose in coffee grounds before and after treatment

[0052] Sample name Lignin(%) Hemicellulose (%) Cellulose(%) Pre-processed coffee grounds 30.3±1.5 51.5±0.5 18.2±0.8 Processed coffee grounds 5.3±0.77 49.8±0.56 44.8±1.2

[0053] Example 4

[0054] The delignified coffee grounds prepared in Example 1 were soaked in a 1 M dilute hydrochloric acid solution, reacted for 5 hours at a temperature of 40° C. and a stirring speed of 500 rpm, the filtrate was filtered out, washed with deionized water until the filtrate was neutral, and dried to obtain polysaccharides.

[0055] Example 5

[0056] The delignified coffee grounds prepared in Example 2 were soaked in a 2M dilute hydrochloric acid solution, reacted for 4 hours at a temperature of 35° C. and a stirring speed of 300 rpm, the filtrate was filtered out, washed with deionized water until the filtrate was neutral, and dried to obtain polysaccharides.

[0057] Example 6

[0058] The delignified coffee grounds prepared in Example 3 were soaked in a 3M dilute hydrochloric acid solution, reacted for 3 hours at a temperature of 30° C. and a stirring speed of 200 rpm, the filtrate was filtered out, washed with deionized water until the filtrate was neutral, and dried to obtain polysaccharides.

[0059] Example 7

[0060] The degree of polymerization of the polysaccharides prepared in Examples 4 to 6 was tested by mass spectrometry. The polysaccharides prepared in Examples 4 to 6 were respectively formed into uniform solutions, and then the liquids were converted into charged aerosol particles, and then analyzed by mass spectrometer to obtain the degree of polymerization of the polysaccharides. The results showed that the degrees of polymerization of the polysaccharides prepared in Examples 4 to 6 were 78 to 100, 59 to 82, and 36 to 57, respectively.

[0061] Example 8

[0062] Into the multifunctional reactor, 30 parts of the polysaccharide prepared in Example 4, 20 parts of 3-formylbutenoic acid, and 10 parts of 1,4-dioxane were added in order by mass. The reactants were heated to 50° C. at a stirring speed of 500 rpm, and the reaction was carried out for 6 hours until the reaction was completed; then, the mixture was heated to 30° C. and distilled at a pressure of 55 mbar using reduced pressure distillation to evaporate 1,4-dioxane and unreacted 3-formylbutenoic acid and collect and store them, the distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30° C. to obtain a purified acrylic acid-modified polysaccharide.

[0063] Example 9

[0064] Into the multifunctional reactor, 35 parts of the polysaccharide prepared in Example 5, 25 parts of 4-aldehyde pentenoic acid, and 15 parts of 1,4-dioxane were added in order by mass. The reactants were heated to 55° C. at a stirring speed of 800 rpm, and the reaction was carried out for 5 hours until the reaction was completed. Then, the mixture was heated to 35° C. and distilled at a pressure of 60 mbar using reduced pressure distillation to evaporate 1,4-dioxane and unreacted 4-aldehyde pentenoic acid and collect and store them. The distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30° C. to obtain a purified acrylic acid-modified polysaccharide.

[0065] Example 10

[0066] Into the multifunctional reactor, 40 parts of the polysaccharide prepared in Example 6, 30 parts of 5-formaldehyde hexenoic acid, and 20 parts of 1,4-dioxane were added in order by mass. The reactants were heated to 60° C. at a stirring speed of 1000 rpm, and the reaction was carried out for 4 hours until the reaction was completed; then, the mixture was heated to 40° C. and distilled at a pressure of 65 mbar using reduced pressure distillation to evaporate 1,4-dioxane and unreacted 5-formaldehyde hexenoic acid and collect and store them, the distilled solution was filtered, the filter residue was collected, and the filter residue was air-dried at 30° C. to obtain a purified acrylic acid-modified polysaccharide.

[0067] Embodiment 11

[0068] The total carboxyl content of the prepared acrylic acid-modified polysaccharide was determined by alkaline hydrolysis and reverse titration, thereby determining the acrylic acid grafting rate of the polysaccharide. 0.5 g of the sample was added to 40 ml (70%) ethanol solution, and the resulting suspension was stirred continuously for 30 minutes. Then 20 ml (0.5 M) NaOH solution was added to the suspension and hydrolyzed at 60° C. for 48 hours. Phenolphthalein was used as an indicator and the unconsumed NaOH was titrated after hydrolysis with HCl (0.5 M) solution.

[0069]

[0070] Where V B is the volume of NaOH, V s is the volume of HCl consumed in titration, C HCl is the concentration of HCl, m is the dry weight of acrylic acid modified polysaccharide, and the results show that the total carboxyl content of the polysaccharides prepared in Examples 4, 5 and 6 are 0.13, 0.16 and 0.17 mmol g, respectively. -1 The total carboxyl content of the acrylic acid-modified polysaccharides prepared in Examples 8, 9 and 10 was 0.89, 1.12 and 0.92 mmol-1g -1 .

[0071] The free carboxyl content of the polysaccharides prepared in Examples 4, 5 and 6 and the acrylic acid-modified polysaccharides prepared in Examples 7, 8 and 9 was determined by conductivity titration. 50 mg of the sample was selected, and then 10 ml (0.01 M) HCl was added and ultrasonic treatment was performed for 4 hours. Finally, the suspension was titrated with NaOH (0.01 M).

[0072]

[0073] In the formula, C NaOH is the concentration of NaOH (0.01M), V NaOH The volume of NaOH required to titrate all the HCl, m is the dry weight of the sample. The results show that the free carboxyl content of the polysaccharides prepared in Examples 4, 5 and 6 is 0.05, 0.08 and 0.12 mmol g, respectively. -1 The free carboxyl contents of the acrylic acid-modified polysaccharides prepared in Examples 8, 9 and 10 were 0.54, 0.97 and 0.68 mmol g, respectively. -1 , that is, the grafting rates of acrylic acid groups of acrylic acid-modified polysaccharides prepared in Examples 7, 8 and 9 were approximately 0.54, 0.97 and 0.68 mmol g, respectively. -1 .

[0074] Example 12

[0075] In a multifunctional reactor, isobutyl acrylate, deionized water, sodium stearate and sucrose fatty acid ester are added in sequence according to the formula weight, and then nitrogen is introduced and stirred at a speed of 500 rpm for 30 minutes to obtain an emulsion, and then acrylic modified polysaccharide is added, and stirring is continued for 30 minutes to obtain a uniform mixed solution, and nitrogen is continued to be introduced for 10 minutes; the introduction of nitrogen is stopped, the temperature is heated to 100°C, and then tert-amyl peroxyacetate is added in the formula amount, and stirring is continued to initiate polymerization reaction, and the temperature is kept for 2 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, maleic anhydride, trimethylolpropane and Sn(Oct)2 are added in sequence, and the temperature is continued to be raised to 140°C, and the temperature is kept for 1 hour to completely dissolve the materials to form a uniform solution, and then the temperature is continued to be raised to 180°C to initiate esterification reaction, and the reaction is carried out for 6 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, samples are taken every 30 minutes for acid value testing, and when the acid value is 50-60 mg KOH / g, stop the reaction; cool to 50°C and keep warm, disperse for 60 minutes at a stirring speed of 8000 rpm, add a formulated amount of deionized water to make the viscosity of the mixed solution 9000cps / 25°C, and then continue stirring for 60 minutes at a stirring speed of 800 rpm to obtain a polysaccharide acrylic resin.

[0076] Table 4 Raw material ratio of Example 12 Synthetic polysaccharide acrylic resin

[0077] Acrylic acid modified polysaccharide 40~50 servings Isobutyl acrylate 10~30 servings Maleic anhydride 20~30 servings Trimethylolpropane 10-15 servings Sodium stearate 3-5 servings Tert-Amyl Peroxyacetate 0.4~0.6 Sucrose fatty acid esters 0.1~0.3 parts <![CDATA[Sn(Oct)2]]> 1~3 servings Deionized water 60~80 servings

[0078] The acrylic acid-modified polysaccharide in Table 4 was prepared by the method described in Example 8.

[0079] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared polysaccharide acrylic resin after film formation (curing at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0080] The VOC of the prepared polysaccharide acrylic resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤42.19.

[0081] The water resistance of the prepared polysaccharide acrylic resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 12.59%.

[0082] The tensile strength of the polysaccharide acrylic resin film (cured at 50°C for 3 hours) was tested by a universal tensile testing machine, and the film strength was 184.57 kPa.

[0083] Example 13

[0084] In a multifunctional reactor, isooctyl acrylate, deionized water, sodium stearyl glutamate and polyglycerol fatty acid ester are added in sequence according to the formula weight, and then nitrogen is introduced and stirred at a speed of 800 rpm for 20 minutes to obtain an emulsion, and then acrylic acid-modified polysaccharide is added, and stirring is continued for 20 minutes to obtain a uniform mixed solution, and nitrogen is continued to be introduced for 8 minutes; the introduction of nitrogen is stopped, the temperature is raised to 105°C, and then the formula amount of tert-butyl hydroperoxide is added, and stirring is continued to initiate a polymerization reaction, and the temperature is kept for 2 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, acetic anhydride, trimethylolethane and antimony trioxide are added in sequence, and the temperature is continued to be raised to 150°C, and the temperature is kept for 0.8 hours to completely dissolve the materials and form a uniform solution, and then the temperature is continued to be raised to 190°C to initiate an esterification reaction, and the reaction is carried out for 5 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, samples are taken every 30 minutes for acid value testing, and when the acid value is 50-60 mg KOH / g, stop the reaction; cool to 50°C and keep warm, disperse for 45 minutes at a stirring speed of 9000 rpm, add the formulated amount of deionized water to make the viscosity of the mixed solution 10000cps / 25°C, and then continue stirring for 45 minutes at a stirring speed of 900 rpm to obtain a polysaccharide acrylic resin.

[0085] Table 5 Raw material ratio of Example 13 Synthetic polysaccharide acrylic resin

[0086] Acrylic acid modified polysaccharide 40~50 servings 2-Ethylhexyl acrylate 10~30 servings Acetic anhydride 20~30 servings Trimethylolethane 10-15 servings Sodium Stearyl Glutamate 3-5 servings Tert-Butyl Hydroperoxide 0.4~0.6 Polyglycerol fatty acid esters 0.1~0.3 parts Antimony trioxide 1~3 servings Deionized water 60~80 servings

[0087] The acrylic acid-modified polysaccharide in Table 5 was prepared by the method described in Example 9.

[0088] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared polysaccharide acrylic resin after film formation (curing at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0089] The VOC of the prepared polysaccharide acrylic resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤42.69.

[0090] The water resistance of the prepared polysaccharide acrylic resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 11.54%.

[0091] The tensile strength of the polysaccharide acrylic resin film (cured at 50°C for 3 hours) was tested by a universal tensile testing machine, and the film strength was 211.95 kPa.

[0092] Embodiment 14

[0093] In a multifunctional reactor, methyl methacrylate, deionized water, potassium hexadecyl phosphate and polyglycerol fatty acid ester are added in sequence according to the formula weight, and then nitrogen is introduced and stirred at a speed of 1000 rpm for 10 minutes to obtain an emulsion, and then acrylic acid-modified polysaccharide is added, and stirring is continued for 10 minutes to obtain a uniform mixed solution, and nitrogen is continued to be introduced for 5 minutes; the introduction of nitrogen is stopped, the temperature is heated to 110°C, and then benzoyl peroxide in the formula amount is added, and stirring is continued to initiate a polymerization reaction, and the temperature is kept for 2 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, terephthalic acid, glycerol and Sn(Oct)2 are added in sequence, and the temperature is continued to be raised to 160°C, and the temperature is kept for 0.5 hours to completely dissolve the materials to form a uniform solution, and then the temperature is continued to be raised to 200°C to initiate an esterification reaction, and the reaction is carried out for 4 hours, during which the generated water vapor is separated by a water separator; after the reaction is completed, samples are taken every 30 minutes for acid value testing, and when the acid value is 50-60 mg When the mixture reaches 400 g / min, the reaction is stopped; the mixture is cooled to 50°C and kept warm, and dispersed for 30 minutes at a stirring speed of 10,000 rpm, and deionized water in a formulated amount is added to make the viscosity of the mixed solution 9,000 to 12,000 cps / 25°C, and then the stirring is continued for 30 minutes at a stirring speed of 1,000 rpm to obtain a polysaccharide acrylic resin.

[0094] In some embodiments, the catalyst may be antimony trioxide, Sn(Oct)2, or a combination thereof.

[0095] Table 6 Raw material ratio of Example 14 Synthetic polysaccharide acrylic resin

[0096] Acrylic acid modified polysaccharide 40~50 servings Methyl Methacrylate 10~30 servings Terephthalic acid 20~30 servings glycerin 10-15 servings Potassium cetyl phosphate 3-5 servings Benzoyl peroxide 0.4~0.6 Polyglycerol fatty acid esters 0.1~0.3 parts <![CDATA[Sn(Oct)2]]> 1~3 servings Deionized water 60~80 servings

[0097] The acrylic acid-modified polysaccharide in Table 6 was prepared by the method described in Example 9.

[0098] According to GB / T 6739-1996 “Coating Hardness Pencil Test Method”, the strength of the prepared polysaccharide acrylic resin after film formation (curing at 50°C for 3 hours) was tested manually. The test results showed that the film strength was >B.

[0099] The VOC of the prepared polysaccharide acrylic resin film was tested according to GB / T 23985-2009 “Paints and varnishes - Determination of volatile organic compound (VOC) content - Difference method”, and the result was VOC≤29.4.

[0100] The water resistance of the prepared polysaccharide acrylic resin film was tested according to GB / T 1727-1992. After immersion for 48 hours, the water absorption rate was 9.69%.

[0101] The tensile strength of the polysaccharide acrylic resin film (cured at 50°C for 3 hours) was tested by a universal tensile testing machine, and the film strength was 203.41 kPa.

[0102] Embodiment 15

[0103] The polysaccharide-based acrylic resin prepared in Examples 12 to 14 was added to different molds and cured at 50° C. for 3 hours to form different shapes, such as Figure 3 As shown, the results show that the polysaccharide-based acrylic resin prepared by the present invention has good plasticity, transparency and flexibility.

[0104] Example 16

[0105] The polysaccharide-based acrylic resin prepared in Examples 12 to 14 was cured at 50°C for 3 hours to form a film, and then subjected to a biodegradation experiment. The film was placed on the soil surface and placed in a natural environment to observe its changes over time, such as Figure 4 As shown, Examples 12 to 14 decomposed after 24 weeks, demonstrating that the polysaccharide-based acrylic resin prepared by the present invention has good biodegradability.

[0106] Technical personnel should note that although the present invention has been described according to the above specific implementation methods, the inventive concept of the present invention is not limited to this invention, and any modification using the inventive concept will be included in the scope of protection of this patent.

Claims

1. A polysaccharide acrylic resin, characterized in that: The polysaccharide acrylic resin is composed of 40-50 parts of acrylic acid-modified polysaccharide, 10-30 parts of acrylic acid monomer, 20-30 parts of polyacid, 10-15 parts of polyol, 3-5 parts of emulsifier, 0.4-0.6 parts of initiator, 0.1-0.3 parts of defoamer, 1-3 parts of catalyst and 60-80 parts of deionized water in parts by weight. The preparation of the acrylic acid-modified micro-nano coffee grounds includes the following steps: S1 impurity removal: soaking coffee grounds in n-hexane, with a mass volume ratio of coffee grounds to n-hexane of 5-10 g:1-10 mL, reacting at 20-30° C. and a mechanical stirring speed of 200-500 rpm for 3-6 hours, filtering and removing the filtrate to obtain the impurity-removed coffee grounds; S2 Delignification: Soak the coffee grounds after impurity removal in a sodium hydroxide solution with a concentration of 5wt% to 12wt%, with a mass volume ratio of coffee grounds to sodium hydroxide of 1 to 10g:1 to 5mL, react at 80 to 100°C and a mechanical stirring speed of 500 to 1000 rpm for 1 to 3 hours, filter, and collect the filter residue; soak the filter residue in 3 to 10wt% hydrogen peroxide, with a mass volume ratio of filter residue to hydrogen peroxide of 5 to 10g:1 to 5mL, adjust the pH value of the mixed solution to 10 to 12, and react at 80 to 100°C for 2 to 5 hours until the filter residue turns white to obtain delignified coffee grounds; S3 acid hydrolysis: soak the delignified coffee grounds in a dilute hydrochloric acid solution with a concentration of 1M to 3M, react for 3 to 5 hours at a temperature of 30 to 40°C and a stirring speed of 200 to 500 rpm, filter out the filtrate, wash with deionized water until the filtrate is neutral, and dry to obtain polysaccharides; S4 acrylic acid-modified polysaccharide: Into a multifunctional reactor, add 30-40 parts of polysaccharide, 20-30 parts of organic acrylic acid aldehyde, and 10-20 parts of 1,4-dioxane in order by mass, heat the reactants to 50-60°C at a stirring speed of 500-1000 rpm, and react for 4-6 hours until the reaction is completed; then use reduced pressure distillation to heat to 30-40°C and a pressure of 55-65 mbar for distillation, evaporate 1,4-dioxane and unreacted organic acrylic acid aldehyde and collect and store them, filter the distilled solution, collect the filter residue, and air-dry the filter residue at 30°C to obtain purified acrylic acid-modified polysaccharide.

2. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The organic acrylic aldehyde in S4 can be a combination of one or more of 3-formylbutenoic acid, 4-formylpentenoic acid and 5-formylhexenoic acid.

3. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The acrylic monomer may be a combination of one or more of methyl acrylate, ethyl acrylate, butyl acrylate, methacrylic acid, methyl methacrylate, isobutyl acrylate, hexyl acrylate, isooctyl acrylate, and lauryl acrylate.

4. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The polyacid may be one or more combinations of phthalic anhydride, terephthalic acid, acetic anhydride and maleic anhydride.

5. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The polyol may be a combination of one or more of glycerol, pentaerythritol, trimethylolethane, and trimethylolpropane.

6. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The emulsifier may be a combination of one or more of sodium stearate, sodium stearyl glutamate and potassium cetyl phosphate.

7. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The initiator can be a combination of one or more of benzoyl peroxide, tert-butyl hydroperoxide, and tert-amyl peroxyacetate.

8. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The defoaming agent can be a combination of one or more of sucrose fatty acid ester and polyglycerol fatty acid ester.

9. A polysaccharide acrylic resin as claimed in claim 1, characterized in that: The catalyst may be a combination of antimony trioxide, Sn(Oct)2 or one or more thereof.

10. The method for preparing a polysaccharide acrylic resin according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: S5: In a multifunctional reactor, acrylic acid monomer, deionized water, emulsifier and defoamer are added in sequence according to the formula weight, and then stirred at a speed of 500 to 1000 rpm for 10 to 30 minutes while introducing nitrogen to obtain an emulsion, and then acrylic acid-modified polysaccharide is added, and stirring is continued for 10 to 30 minutes to obtain a uniform mixed solution, and nitrogen is continued to be introduced for 5 to 10 minutes; S6: Stop introducing nitrogen, heat to 100-110°C, then add the formulated amount of initiator, continue stirring evenly to initiate the polymerization reaction, and keep warm for 2 hours, during which time the generated water vapor is separated by a water separator; S7 After the reaction is completed, add polyacid, polyol and catalyst in sequence, continue to heat to 140-160°C, keep warm for 0.5-1 hour, so that the materials are completely dissolved to form a uniform solution, and then continue to heat to 180-200°C to initiate esterification reaction, react for 4-6 hours, during which the generated water vapor is separated by a water separator; S8 After the reaction is completed, samples are taken every 30 minutes for acid value testing. When the acid value is 50-60 mg KOH / g, the reaction is stopped; the temperature is lowered to 50°C and kept warm, and dispersed for 30-60 minutes at a stirring speed of 8000-10000 rpm, and deionized water is added in a formula amount so that the viscosity of the mixed solution is 9000-12000 cps / 25°C, and then the stirring is continued for 30-60 minutes at a stirring speed of 800-1000 rpm to obtain a polysaccharide acrylic resin.

Citation Information

Patent Citations

  • Coffee residue-based alkyd resin and preparation method thereof

    CN118240188A

Cited By

  • Polysaccharide acrylic resin and preparation method thereof

    CN120059093A